2017
DOI: 10.1080/07315724.2017.1335250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two β-Alanine Dosing Protocols on Muscle Carnosine Elevations

Abstract: Results of this investigation indicate that a BA supplementation protocol of 12 g/d, using a sustained-release formulation, can accelerate the increase in carnosine content in skeletal muscle while attenuating paresthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 32 publications
0
45
0
3
Order By: Relevance
“…A recent investigation by Church et al. () demonstrated that a 2 week supplement duration of 12 g/day of BA increased intramuscular carnosine content to the same extent as 6 g/day taken for 4 weeks. In addition, the greater supplement dose was not associated with any greater risk for adverse effects (Church et al.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…A recent investigation by Church et al. () demonstrated that a 2 week supplement duration of 12 g/day of BA increased intramuscular carnosine content to the same extent as 6 g/day taken for 4 weeks. In addition, the greater supplement dose was not associated with any greater risk for adverse effects (Church et al.…”
Section: Introductionmentioning
confidence: 95%
“…Most studies examining the beneficial effects of BA supplementation on performance range from 4 to 8 weeks in duration (Hoffman et al 2018), which may not be practical for use in military personnel with short notice before a mission. A recent investigation by Church et al (2017) demonstrated that a 2 week supplement duration of 12 g/day of BA increased intramuscular carnosine content to the same extent as 6 g/day taken for 4 weeks. In addition, the greater supplement dose was not associated with any greater risk for adverse effects (Church et al 2017).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Three-level mixed effects models were used to quantify the effects of supplementation dose. Insufficient data were available to allow investigation of the interaction between daily dose and intervention duration and so the total cumulative dose ingested was selected as the primary outcome, which previous research has identified as being more influential than either daily dose or intervention duration [16,19,20]. Subset analyses using study covariates were used to assess the effects of sex, age or measurement method on the main effect of BA supplementation.…”
Section: Methodsmentioning
confidence: 99%